TATA RUANG KANTOR KAITANNYA DENGAN KINERJA KARYAWAN PT ISPAT INDO SIDOARJO - EKAWATI, NINA (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2013)
The purpose of this study is to obtain a description of find out the impact of the Office layout for the employess performance. The research is descriptive method quantitative. Data was collected using the quesioner technique, documents and interviews.The results showed that the main office layout variable in PT Ispat Indo Sidoarjo entry in the excellent category (57,9%). Meanwhile the employee performance variableentry in good category (61,4%). Based on a test of office layout correlation between the employee performance was the relationship meaning 0,384 weak. As well as the layout office gave a contribution to the employee performance of 14.8%, 85,2% while the rest were determined by other factors. This shows that there was impact, although low between the office layout on employee performance at PT Ispat Indo Sidoarjo.It can be concluded that the office layout has an impact on employee performance.     Key Word : Office Layout, Employees Performance